The challenges and conservation efforts of cultural landscape in the Malay traditional village - Harun, Nor Zalina; Abdullah, Fadzidah; Hj Mohd Ariffin, Noor Aziah (2017)
The cultural landscape is regarded as being of the most complex designs which involves interactions between man, nature, cultural values and the associated built environment. Issues relating to the degradation of the cultural landscape are often caused by rapid urbanisation and industrialisation. The traditional Malay Landscape exists through harmoniously balanced interactions between man, nature and culture together with the traditional house. This type of landscape contains unique and interesting features that have to be preserved as one of the most important cultural heritage sites. However, it is evident that the preservation of heritage in Malaysia tends to focus more on architectural buildings rather than adopting a holistic approach that includes the surrounding environment of where the building is located. Nevertheless, the absence of such approach has contributed towards the loss of the traditional Malay Landscape. This study highlights the challenges in the preservation of the traditional Malay Landscape by focusing on the preservation of a traditional house compound. The first objective is to identify the various challenges and threats concerning the preservation of the traditional Malay Landscape. The second objective is to study the method of protecting the heritage of the traditional Malay Landscape. The research employs a qualitative approach which involves site visits, interviews, and document analysis concerning the research topic. The old Malay villages located in Tumpat, Kelantan and Alor Gajah, Melaka have been selected for the study of the sites. The findings reveal that the challenges include four underlying aspects; 1) Inappropriate uses, 2) Ownership Problems, 3) Inadequate fund and consultation and finally 4) Current development trends. The study concludes that the traditional Malay Landscape is facing numerous challenges and threats in terms of its physical characteristics, environmental aspects and cultural values. In addition, the study reveals that traditional Malay landscape is not seen here as an integrating, holistic concept. As times and ownership changes, layout and significance will be changed and so does the maintenance standard.